2017
DOI: 10.1371/journal.pone.0173768
|View full text |Cite|
|
Sign up to set email alerts
|

Mental health and adjustment to juvenile idiopathic arthritis: Level of agreement between parent and adolescent reports according to Strengths and Difficulties Questionnaire and Adolescent Outcomes Questionnaire

Abstract: The aims of this study were threefold. Firstly, to analyze the psychometric properties of the Polish-language Pediatric Outcomes Data Collection Instrument (PODCI) questionnaire in the self-report Adolescent Outcomes Questionnaire (adolescents, 11–18 years of age) and in the parent-report Adolescent Outcomes Questionnaire (completed by a parent or guardian of an adolescent aged 11–18 years). Secondly, to determine the level of agreement between parents and adolescents in rating dysfunction in juvenile idiopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In the domain of mental/physical health, parent-child agreement ranged from slight to moderate. Regarding behavioral strengths and difficulties, the overall agreement between child and parent reports was fair and, therefore, slightly lower than the agreement reported in previous studies [18][19][20][21][22][23]. In line with other studies [22,24,25], Table 4.…”
Section: Plos Onesupporting
confidence: 76%
See 2 more Smart Citations
“…In the domain of mental/physical health, parent-child agreement ranged from slight to moderate. Regarding behavioral strengths and difficulties, the overall agreement between child and parent reports was fair and, therefore, slightly lower than the agreement reported in previous studies [18][19][20][21][22][23]. In line with other studies [22,24,25], Table 4.…”
Section: Plos Onesupporting
confidence: 76%
“…Regarding evaluations of mental/physical health of children, several studies have investigated parent-child agreement in reporting behavioral difficulties [18][19][20][21][22][23][24][25][26][27]. Overall, in these studies, parent-child agreement was reported to be moderate [18][19][20][21][22] to high [23]. Whereas most of the studies observed higher agreement in reporting with regard to externalizing problems [22,24,25], others found higher agreement for internalizing problems [20] or no difference for externalizing and internalizing problem behavior [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents with Type 1 Diabetes (n=7) and HIV (n=4) constituted half of the total number of studies. Other conditions were Asthma [34,35], Cerebral Palsy [36,37], Cystic Fibrosis [38,39] and Chronic Pain [40,41] with two studies each; with single studies on Congenital Heart Disease [42], Sickle cell disease [34], Cancer [38], Adolescent Idiopathic Scoliosis [43], Juvenile Idiopathic Arthritis [44], Strabismus and Short Stature [45]. Chronic Disease (unspeci ed by authors) [35].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Six of the instruments included are aimed at measuring symptoms of mental health or screening for emotional and behavioural problems. These are the Strength and Di culties Questionnaire (SDQ) [43,44,49,54,57]; Child Depression Inventory instruments (CDI & CDI-short form) [47,48]; Center for Epidemiological Studies Depression (CES-D) [51]; and the Revised Children's Manifest Anxiety Scale [47] and the Beck Hopelessness scale [48].…”
Section: Instruments Measuring Symptoms Of Mental Healthmentioning
confidence: 99%